2012
DOI: 10.2217/fmb.12.38
|View full text |Cite
|
Sign up to set email alerts
|

Otitis Media

Abstract: Otitis media represents a broad spectrum of disease, which include acute otitis media and otitis media with effusion. As immunization with the pneumococcal conjugate vaccine has become more widespread, the microbiological landscape of otitis media has changed, which affects the treatment options facing clinicians worldwide. This review discusses the diagnosis and medical management of acute and chronic suppurative otitis media, the changes noted over the past decade, and briefly expounds on the surgical manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 172 publications
0
36
0
4
Order By: Relevance
“…The importance of other environmental factors cannot be underestimated in the pathogenesis of AOM; Paternal smoking is one of OM risk factors [1,3,8,10,14]; it causes mucosal inflammation, goblet hyperplasia and an increase in the production of mucus, by this it impairs mucosal immunity and increases bacterial colonization by enhancing bacterial binding to respiratory epithelium [1,10]. Children of mothers who smoked during pregnancy and stopped after delivery still have higher incidence of AOM [10].…”
Section: Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…The importance of other environmental factors cannot be underestimated in the pathogenesis of AOM; Paternal smoking is one of OM risk factors [1,3,8,10,14]; it causes mucosal inflammation, goblet hyperplasia and an increase in the production of mucus, by this it impairs mucosal immunity and increases bacterial colonization by enhancing bacterial binding to respiratory epithelium [1,10]. Children of mothers who smoked during pregnancy and stopped after delivery still have higher incidence of AOM [10].…”
Section: Pathogenesismentioning
confidence: 99%
“…Children of mothers who smoked during pregnancy and stopped after delivery still have higher incidence of AOM [10]. Children with bottle feeding is another well known risk factor [1,3,8,10]; it is believed that passive immunity through the breast milk gives some protection [1], bottle-fed infants have higher nontypeable Haemophilus influenzae prevalence and lower immunoglobulin G antibodies [8]. Some studies found a role of Gastro esophageal reflux (GERD) disease [1,18]; GERD is found in 62.9% of patient with rOM.…”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2] Nasal and nasopharyngeal pathologies have long been recognized as important factors in the pathogenesis of otitis media. It has been traditionally hypothesized that a mass in the nasopharynx causes an obstacle to airf low through the Eustachian tube (ET), thereby a negative pressure in the middle ear followed by an effusion.…”
mentioning
confidence: 99%